The mechanism of small wear particles entrainment in friction under boundary lubrication - Tokoroyama, Takayuki; Okashita, Masahiro; Zhang, Ruixi; Murashima, Motoyuki; Tsuboi, Ryo; Yoshida, Takuji; Shiomi, Hiroshi; Umehara, Noritsugu (Frontiers in Mechanical Engineering, 2024)
When the lubricating oil flowing between the contact surfaces contains simulated wear particles, it is considered that there is a high possibility for the particles to enter between the contact surfaces if the particles are present on the disk side in a friction test between a fixed ball and a rotating disk. For particles with a diameter of 0.8 μm, it has been previously shown that the entrainment frequency changes with the outside oil film thickness, but the effect of the disk material on the amount of particle deposition and the visualization of particle movement direction due to vortices generated between the contact surfaces had not been performed. In this study, by using SiO2 disks and sapphire disks with different Hamaker constants, the effect on the amount of particle deposition in front of the contact surfaces was experimentally clarified by changing the van der Waals forces acting between the particles and the disks. Additionally, assuming that vortices generated in the oil film between the contact surfaces move the particles to the disk surface side, the flow direction of the lubricating oil was visualized using Navier-Stokes simulation.